Effects of transcranial magnetic stimulation on sleep structure and quality in children with autism - Yan, Juan; Zhang, Yan; Wang, Junjie; Zhu, Guidong; Fang, Kaijie (Frontiers in Psychiatry, 2024)
Introduction: Transcranial magnetic stimulation (TMS) can influence the excitability of neuronal cells in stimulated areas, leading to improvements in sleep and other autistic symptoms. Studies on TMS in treating sleep disorders associated with ASD are limited. So, we aimed to explore the effects of TMS on sleep structure and quality in children with ASD. Methods: Between Jan. 2020 and Dec. 2021, 60 children with ASD were selected and randomly divided into the active and sham TMS treatment groups, while 30 healthy children of the same age as controls. The active TMS group received bilateral low-frequency (0.5 Hz) TMS targeting the dorsolateral prefrontal cortex on both sides, whereas the sham TMS group received sham stimulation with the same stimulation time and location. Both groups were treated for 6 weeks, the participants were assessed using the Sleep Disturbance Scale for Children (SDSC) before treatment, at 3 weeks, and at 6 weeks of intervention. Independent sample t- and difference t-tests were used for statistical analysis of the data. Results: No significant differences were observed in general demographic variables, between the ASD and control groups (P>0.05). Independent sample t-test showed that the total SDSC score, difficulty falling asleep, sleep maintenance, awakening disorders, sleep-wake transition disorders, excessive daytime sleepiness, and nocturnal hyperhidrosis scores were significantly higher in the ASD group (P<0.05). Before treatment, no significant differences were observed in the factor or total SDSC scores between the sham TMS and the active TMS group (P>0.05). After 15 and 30 treatment sessions, the total SDSC score, difficulty falling asleep, sleep maintenance, sleep-wake transition disorders, and excessive daytime sleepiness scores were significantly higher in the sham TMS group (P<0.05). The difference t-test showed that after 30 treatment sessions, the reduction rates of total SDSC score, difficulty falling asleep, sleep maintenance, awakening disorders, sleep-wake transition disorders, excessive daytime sleepiness, and nocturnal hyperhidrosis dimensions were significantly higher in the active TMS group (P<0.05). Conclusion: Low-frequency TMS targeting the dorsolateral prefrontal cortex in children with ASD can effectively improve their sleep status, and significant improvement can be achieved after 6 weeks (30 sessions) of treatment.